Different Views about the Nature of Gender-Related Asymmetries in Tasks Based on Biological or Artefact Categories - Guido Gainotti; Francesca Ciaraffa; Maria Caterina Silveri; Camillo Marra (Behavioural Neurology)
Sex-related asymmetries in the ability to process different semantic categories have been reported both in normal subjects and in brain-damaged patients, but the nature of these asymmetries is still controversial. Some authors suggest that these differences might be due to social-role related familiarity factors, whereas others attribute them to inborn neural differences rooted in evolution. Drawing in part on this second line of thought, some authors have suggested that gender-related asymmetries might be due to differences in stimulus processing between men and women, namely, to the tendency of females to focus mainly on perceptual features and of males to focus equally on both perceptual and functional features. To test this hypothesis, we asked 53 male and 65 female undergraduate students to evaluate the relevance of a number of perceptual and functional features in the representation of various kinds of biological and artefact categories. Contrary to the hypothesis, evaluation of the weight of different sources of knowledge in representing living and artefact categories was similar in males and females.